Traveling Bodies: Interdisciplinary Perspectives on Traveling as an Embodied Practice, edited by Nicole Maruo-Schröder, Sarah Schäfer-Althaus, and Uta Schaffers (A Book Review) - Szołtysek, Julia (Review of International American Studies, 2024)
The present review looks at the recent contribution to the Routledge Research in Travel Writing series—Traveling Bodies: Interdisciplinary Perspectives on Traveling as an Embodied Practice, edited by Nicole Maruo-Schröder, Sarah Schäfer-Althaus, and Uta Schaffers. The review discusses the contents of the volume, the concept and methodology employed in the work, as well as the major aspects pertaining to its position within the broad field of travel writing. It offers an evaluation of the originality of the collection and assesses the quality of the contributions included in the volume, highlighting how the gathered articles enrich the ongoing academic debate on travel, travel writing and the embodied experience of mobility and movement. The present review looks at the recent contribution to the Routledge Research in Travel Writing series—Traveling Bodies: Interdisciplinary Perspectives on Traveling as an Embodied Practice, edited by Nicole Maruo-Schröder, Sarah Schäfer-Althaus, and Uta Schaffers. The review discusses the contents of the volume, the concept and methodology employed in the work, as well as the major aspects pertaining to its position within the broad field of travel writing. It offers an evaluation of the originality of the collection and assesses the quality of the contributions included in the volume, highlighting how the gathered articles enrich the ongoing academic debate on travel, travel writing and the embodied experience of mobility and movement.